Antioxidant supplementation in female ruminants during the periconceptional period: a review - Juan González-Maldonado (Universidad de Antioquia, 2018)
Stress is the result of an imbalance between free radicals and antioxidants. Under normal physiological conditions, free radicals are involved in reproductive events such as cell cycle activation, ovulation and luteolysis. However, when an overproduction of free radicals surpasses antioxidant capacity, oxidative damage, reproductive anomalies and diminished fertility occur. Supplementation with antioxidants prevents oxidative damage and can be incorporated into reproductive management to improve fertility in females. Selection of the preovulatory follicle, ovulation, fertilization, embryo development and formation of the corpus luteum occur during the periconceptional period. This is a dynamic period and the events are susceptible to oxidative stress damage. Therefore, the objective of this review is to discuss the effect of oxidative stress on reproductive events during the periconceptional period, as well as to address antioxidant supplementation during this period.